2016
DOI: 10.1186/s12884-016-1153-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in women with Eisenmenger’s syndrome: a case series from west China

Abstract: BackgroundEisenmenger’s syndrome (ES) consists of pulmonary hypertension with a reversed or bidirectional shunt at the atrioventricular, or aortopulmonary level.The cardiovascular changes that occur during the pregnancy contribute to the high maternal morbidity and mortality in patients with ES. This study is to assess maternal and fetal outcomes in patients with ES.MethodsThis study is a retrospective analysis of 11 pregnancies in women with ES who delivered at a tertiary care center in west China between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
(29 reference statements)
6
29
0
6
Order By: Relevance
“…12 Similar to our finding, the presence of Eisenmenger syndrome was associated with worst outcome, both for maternal and fetal survival. 12 RV dysfunction and failure are also associated with worsened outcome for pregnant women with CHD-PH. 13 Reduced TAPSE (mean TAPSE < 19 mm) was observed in nonsurvivors, which indicated the reduced RV systolic function during current pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…12 Similar to our finding, the presence of Eisenmenger syndrome was associated with worst outcome, both for maternal and fetal survival. 12 RV dysfunction and failure are also associated with worsened outcome for pregnant women with CHD-PH. 13 Reduced TAPSE (mean TAPSE < 19 mm) was observed in nonsurvivors, which indicated the reduced RV systolic function during current pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…The advantages of a Cesarean delivery include avoiding hemodynamic instability related to uterine contractions and pain, but this should be performed by an expert specialist multidisciplinary team. 20,21 Two patients had unplanned general anesthesia in this study and died. As in other studies, general anesthesia was associated with a high risk of death in pregnant patients with PAH-CHD, especially in ES, attributable to the adverse effects of intubation and associated hemodynamic changes.…”
Section: Discussionmentioning
confidence: 81%
“…We included 13 studies, with a total of 272 pregnancies in 258 women with PAH. 5 17 A total of 214 pregnancies were advanced beyond 20 weeks. The description of included studies is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the eight studies that reported the cause of prematurity, most were iatrogenic; 84% ( n = 63/75) secondary to a planned premature delivery usually for maternal indications. 5 , 6 , 9 , 11 , 12 , 14 , 16 , 17 In the eight studies that reported birthweights, 5 7 , 9 , 10 , 13 , 14 , 17 the mean birthweight was at 1922 ± 292 g and 36% of babies were reported to be small for gestational age.…”
Section: Resultsmentioning
confidence: 99%